ANALISIS UNSUR INTRINSIK PUISI AKU KARYA CHAIRIL ANWAR - Widiyanti Ningrum (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
Literary works have their own characteristics, especially the characteristics of literary works in the form of poetry. Typical of poetry when compared with other literature is a brief litelary work. It has to do with taste. Majas and figurative language, and it must also be master of reading. If the reader has known come to know, know and understand a poem, so that it is hoped that he will be able to put it into his heart. researchers chose to analyze the litelary work of the poem, Because here were some people who experienced a similar event such as the of striving to achieve a desire because to be achieved. This study uses a qualitative descriptive method. The purpose of this study to analyze the intrinsic element in poetry by Chairil Anwar which was described thoroughly from the 7 elements, from the results of this study there are several intrinsic poetry elements including 1) analizyng the intrinsic of poetry 2) diction 3) taste 4) tone 5)atmosphere 6) maje 7) message. The results of the intrinsic of poetry that researchers have carried out are the meanings contained in the poem I which describe the courage of a person in struggling and having hight spirits despite the many obstacles that come up.